2022
DOI: 10.1017/erm.2021.34
|View full text |Cite
|
Sign up to set email alerts
|

Divide and conquer: spatially fractionated radiation therapy

Abstract: Spatially fractionated radiation therapy (SFRT) challenges some of the classical dogmas in conventional radiotherapy. The highly modulated spatial dose distributions in SFRT have been shown to lead, both in early clinical trials and in small animal experiments, to a significant increase in normal tissue dose tolerances. Tumour control effectiveness is maintained or even enhanced in some configurations as compared with conventional radiotherapy. SFRT seems to activate distinct radiobiological mechanisms, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 132 publications
0
56
0
Order By: Relevance
“…The two main variants of SFRT with photons that have been studied and implemented include GRID radiotherapy (GRID RT) and lattice radiotherapy (LRT)鈥攁 3D configuration of GRID, delivering spherical subvolumes of a high dose within the tumour. Ultra-high-dose-rate methods, including FLASH and microbeam radiotherapy, and LRT are beyond the scope of this review and can be found elsewhere in the literature [ 2 , 10 , 31 , 38 , 39 , 40 ].…”
Section: Preclinical and Clinical Evidence With Spatially Fractionate...mentioning
confidence: 99%
“…The two main variants of SFRT with photons that have been studied and implemented include GRID radiotherapy (GRID RT) and lattice radiotherapy (LRT)鈥攁 3D configuration of GRID, delivering spherical subvolumes of a high dose within the tumour. Ultra-high-dose-rate methods, including FLASH and microbeam radiotherapy, and LRT are beyond the scope of this review and can be found elsewhere in the literature [ 2 , 10 , 31 , 38 , 39 , 40 ].…”
Section: Preclinical and Clinical Evidence With Spatially Fractionate...mentioning
confidence: 99%
“…Spatially fractionated radiation therapy (SFRT) is an unconventional radiotherapy (RT) that has been used clinically since the 1970s. In parallel, SFRT has also been the subject of preclinical research for decades [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. In recent years, SFRT has attracted renewed and enthusiastic interest in radiation oncology [ 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, SFRT has attracted renewed and enthusiastic interest in radiation oncology [ 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Compelling data from preclinical research and some, but still limited, clinical studies have indicated that SFRT may lead to a very high therapeutic ratio compared with conventional RT [ 5 , 6 , 7 ]. Instead of the seamless dose distribution of conventional RT, SFRT has its signature dose distribution, which is characterized by a juxtaposition of many small dose hot spots and cold spots in space in an oscillating pattern [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been known for quite a long time now that the use of heterogeneous spatially fractionated beams that deliver a non-uniform dose distribution to the target mass can lead to an advantage, particularly in terms of normal tissue sparing, while maintaining an anti-tumour effect (Prezado 2022 ). Examples of such spatially fractionated radiation treatments are grid therapy and the still pre-clinical mini- and microbeam therapy approaches.…”
Section: Introductionmentioning
confidence: 99%